Pengaruh Digital Marketing dan Inovasi Produk terhadap Pendapatan Pedagang Cemilan Pasar Tradisional Desa Balung Kulon - Ratnawati, Irma; Yasin, Mochammad (KUBIS, 2024)
Looking at the problems of traditional market traders caused by the development of digital marketing which has an impact on the economy which is not optimal for traditional market snack traders. The purpose of this study is to determine the effect of digital marketing on the income of snack traders and to determine the effect of product innovation on traditional market snack traders in Balung Kulon Village, Balung District, Jember Regency. This research methodusing quantitative descriptive analysis and purposive sampling method with a total sample of 30 respondents. Data analysis with interviews and questionnaires. The results showed that in digital marketing the results of the Multiple Linear Regression analysis obtained a value of -170,022.616, this can be seen from the multiple regression coefficient value, which means that every time there is an increase in the x1 variable by 1%, the income of traditional market snack traders will decrease by Rp. 170,022.616, while for product innovation the results of multiple linear analysis get a value of Rp. 556,952.874, this can be seen from the multiple regression coefficient which means that every time there is an increase in variable X2 of 1 rupiah, the income of traditional market snack traders in Balungkulon Village will increase by Rp. 556,952,874. Based on research in the field, it was found that digital marketing efforts and product innovation carried out by snack traders in the Balungkulon Village traditional market can affect the income of snack traders.